Fatal dissemination of cytomegalovirus after bone marrow transplantation. Issue 9 (September 1981) - Craft, AW; Hamilton, PJ; McQuillin, J; Scott, DJ; Walker, W
Abstract : The clinical course and necropsy findings are described of an 11-year-old child found to have active cytomegalovirus infection at the time of bone marrow transplantation for acute lymphoblastic leukaemia. Attention is drawn to the presence of primitive mononuclear cells of uncertain origin in the regenerating bone marrow.